Unravelling the Impact of Food Insecurity on the Prevalence of Double Burden of Malnutrition among Children of Pakistan - Sultan, Rabia; Iram, Afshan (iRASD Journal of Economics, 2023)
Food insecurity is a major cause of double burden of malnutrition among children in developing world. Despite being self-sufficient, Pakistan contains 60% of food insecure population. Moreover, about half of under-five children are stunted and one-tenth are overweight. The coexistence of undernutrition and over nutrition among under-five children is not well investigated in the same household. This study unravels the impact of food insecurity on the prevalence of double burden of malnutrition among under-five children by employing 2018 Pakistan Demographic Health Survey data and hierarchical mixed effect logistic regression. A sample of 3,625 6-29 months old children was included. The results state that child food insecurity increases the risk of double burden (OR: 1.49, CI: 1.03-2.16) after adjusting for household and community level socioeconomic and demographic factors. Food security and nutrition programs should be targeted to prevent early childhood double burden of child malnutrition to avoid future productivity losses.